2022
DOI: 10.1371/journal.pone.0278480
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of structured exercise programmes on physiological and psychological outcomes in adults with inflammatory bowel disease (IBD): A systematic review and meta-analysis

Abstract: Background Exercise has been suggested to counteract specific complications of inflammatory bowel disease (IBD). However, its role as a therapeutic option remains poorly understood. Therefore, we conducted a systematic review and meta-analysis on the effects of exercise in IBD. Methods Five databases (MEDLINE, Embase, CINAHL, CENTRAL and SPORTDiscus) and three registers (Clinicaltrials.gov, WHO ICTRP and ISRCTN) were searched from inception to September 2022, for studies assessing the effects of structured e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 64 publications
(439 reference statements)
0
8
0
1
Order By: Relevance
“…Previous reviews were either not recent 46 or included trials published prior to the recent advances in medical therapies. 47 While narrative reviews 48 may come to similar conclusions as systematic reviews, they lack the same level of methodological rigor or transparency.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reviews were either not recent 46 or included trials published prior to the recent advances in medical therapies. 47 While narrative reviews 48 may come to similar conclusions as systematic reviews, they lack the same level of methodological rigor or transparency.…”
Section: Discussionmentioning
confidence: 99%
“…Таким образом, с позиции доказательной медицины, проведённые до 2022 года исследования предоставляют лишь предварительные данные о положительном влиянии упражнений на здоровье костей, мышечную функцию, психологическое благополучие, утомляемость, кардиореспираторную выносливость, состав тела, иммунные параметры и воспалительные биомаркеры [54]. Однако гипотеза о влиянии ФА на патогенные звенья большинства ХНИЗ полностью подтверждена: ФУ способны модифицировать воспалительный статус субъекта за счет снижения уровней провоспалительных цитокинов, включая IL-1, IL-6 и TNF-α.…”
Section: заключениеunclassified
“…Physical activity is defined as any bodily movement that substantially increases energy expenditure [11]. Some studies have suggested higher levels of physical activity may be associated with more favorable psychological health outcomes in those with IBD [12,13]. A recent narrative review described how greater time spent in physical activity may also be associated with decreased IBD prevalence, decreased IBD symptoms [14], and possibly, maintenance of disease remission [15].…”
Section: Introductionmentioning
confidence: 99%